Application of the Resource Sharing Innovation Model in Addressing the High Unemployment Rate in a Sustainable Way - Bambang Dwi Suseno; Furtasan Ali Yusuf; Syamsul Hidayat; Dewi Surani (Universitas Mercu Buana, 2022)
Objectives: The current study tries to explore the novelty of the resource sharing innovation variable as a mediating variable to solve several contradictions regarding the correlation between vocational school graduates and industrial human competitiveness. Such exploration also aims to offer a new viewpoint regarding two variables namely the skill development center and training revolving fund.Methodology: The current study applied Research and Development (R&D) method which involved apprentice learners as the samples, who were selected from certain companies which were inviting apprentice learners who graduated from vocational schools. Further data processing was performed through the software of IBM AMOS 2.2.Finding: The study results were further analyzed in the form of triangulation for finding confirmation from certain officers who managed apprenticeship programs at the seven companies involved. The readiness toward Resource Sharing Innovation (RSI) was found to have a significant effect on the Industrial People Competitiveness.Conclusion: The study conclusion made based on study findings indicated evidence that the novelty of Resource Sharing Innovation (RSI) was able to support the industrial human competitiveness.